Pengembangan Desain Model Pembelajaran Virtual Flipped Classroom - Rita Mariyana (Jurnal Pembelajaran Inovatif, 2020)
This study aims to develop a virtual learning model design in the form of a flipped classroom virtual learning program application. This research and development is carried out to improve the quality of learning by developing a flipped classroom virtual learning design that is easy to understand, easy to use so that students can quickly understand the teaching material in the online lecture process. The research and development approach used in this research was purposive sampling technique for students who participated in the online system learning process. To describe the result of research from the improvement of learning design of flipped classroom based on virtual media, this research utilised a descriptive method, with a purposive sampling technique that studied active students in Early Childhood Teacher Education Program (henceforth-ECTE Program). Faculty of Education, Universitas Pendidikan Indonesia. Data from students’ final examination scores, questionnaires, interviews were analyzed using quantitative and qualitative approach. The final products were a flipped classroom software along with its virtual based classroom design.